Flattening the Curve: Glasgow Improvisers Orchestra’s Use of Virtual Improvising to Maintain Community During the COVID-19 Pandemic - MacDonald, Raymond; Birrell, Ross (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Musicians/academics Raymond MacDonald and Ross Birrell discuss the technological challenges and affordances of improvising over Zoom with the Glasgow Improvisers Orchestra.